A review of serious adverse effects under treatment with checkpoint inhibitors - Heinzerling, Lucie; Goldinger, Simone M. (Current Opinion in Oncology, 2017)
PURPOSE OF REVIEW: The aim of this article is to raise awareness of physicians for the serious side-effects of immune-checkpoint blocking antibodies. As checkpoint inhibitors can induce severe side-effects and are increasingly being used also in subspecialties besides dermatology and oncology, with less experience with these drugs available, knowledge has to be spread. Early recognition and adequate management is essential. RECENT FINDINGS: Recent reports on side-effects document cases of serious side-effects involving all organ systems. These include formerly little referenced and life-threatening side-effects such as cardiotoxicity and neurotoxicity. Furthermore, important additional findings are the inclusion of CMV reactivation in the differential diagnosis or the side-effect profile in special patient populations, that is, in transplant patients, patients with autoimmune disease or previous toxicity to ipilimumab. SUMMARY: Checkpoint inhibitor treatment induces a wide range of serious side-effects. However, with prompt diagnosis and adequate treatment these can mostly be safely managed. Documentation and reporting of serious side-effects remains important to share knowledge and thus ensure optimal patient care.
EVALuna2:34336